Isolation of endophytic fungi from Cotoneaster multiflorus and screening of drought-tolerant fungi and evaluation of their growth-promoting effects - Lü, Zeng-Wei; Liu, Hao-Yang; Wang, Chen-Lu; Chen, Xue; Huang, Yi-Xiao; Zhang, Miao-Miao; Huang, Qiu-Liang; Zhang, Guo-Fang (Frontiers in Microbiology, 2023)
In the context of climate change and human factors, drought problem is particularly serious, and environmental pollution caused by the abuse of chemical fertilizers and pesticides is increasingly serious. Endophytic fungi can be used as a protection option, which is ecologically friendly, to alleviate abiotic stresses on plants, promote plant growth, and promote the sustainable development of agriculture and forestry. Therefore, it is of great significance to screen and isolate endophytic fungi that are beneficial to crops from plants in special habitats. In this study, endophytic fungi were isolated from Cotoneaster multiflorus, and drought-tolerant endophytic fungi were screened by simulating drought stress with different concentrations of PEG-6000, and the growth-promoting effects of these drought-tolerant strains were evaluated. 113 strains of endophytic fungi were isolated and purified from different tissues of C. multiflorus. After simulated drought stress, 25 endophytic fungi showed strong drought tolerance. After ITS sequence identification, they belonged to 7 genera and 12 species, including Aspergillus, Fusarium, Colletotrichum, Penicillium, Diaporthe, Geotrichum and Metarhizium. According to the identification and drought stress results, 12 strains of endophytic fungi with better drought tolerance were selected to study their abilities of dissolving inorganic phosphorus, dissolving potassium feldspar powder and producing indole-3-acetic acid (IAA). It was found that the amount of dissolved phosphorus of 7 strains of endophytic fungi was significantly higher than that of CK, and the content of soluble phosphorus was 101.98-414.51 µg. mL -1 ; 6 endophytic fungi had significantly higher potassium solubilization than CK, and the content of water-soluble potassium ranged from 19.17-30.94 mg•L -1 ; 6 strains have the ability to produce IAA, and the yield of IAA is between 0.04-0.42 mg. mL -1 . This study for the first time identified the existence of endophytic fungi with drought tolerance and growth-promoting function in C. multiflorus, which could provide new strain resources for plant drought tolerance and growth promotion fungi. It also provides a theoretical basis for the subsequent application of endophytic fungi of C. multiflorus in agricultural and forestry production to improve plant tolerance.